Investigation of the qualitative composition and quantitative content of flavonoids in the herbal antidiabetic collections № 3 and № 4 by the method of HPLC - A. O. Savych; S. M. Marchyshyn; L. O. Kravchuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
Pharmacotherapy of diabetes mellitus is an extremely important problem of medicine and pharmacy due to its deficient safety and imperfection in maintaining optimal glycemia, frequent changes of which lead to the development of diabetes angiopathies. Therefore, the optimization of existing treatments with herbal collections is appropriate because of their low toxicity and the complex effect of the number of biologically active substances on the pathogenesis of diabetes and its complications.